2020
DOI: 10.1038/s41598-020-65295-4
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of Faraday-like body waves in vibrated living earthworms

Abstract: Biological cells and many living organisms are mostly made of liquids and therefore, by analogy with liquid drops, they should exhibit a range of fundamental nonlinear phenomena such as the onset of standing surface waves. Here, we test four common species of earthworm to demonstrate that vertical vibration of living worms lying horizontally on a flat solid surface results in the onset of subharmonic Faraday-like body waves, which is possible because earthworms have a hydrostatic skeleton with a flexible skin … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Thirdly, although considerable attention has been paid to the long-term temporal stability of certain kinds of AFCs and conclusions have been drawn regarding their applicability to resolve specific problems such as precision underwater measurement, the stability of AFCs of the other kinds has not been investigated in great detail. While filling this knowledge gap is likely to be one of the future directions in AFC research, the lack of long-term stability may be inconsequential in some applications such as, for example, sensing and imaging in in vivo biological environments [ 7 , 183 ] that evolve in time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, although considerable attention has been paid to the long-term temporal stability of certain kinds of AFCs and conclusions have been drawn regarding their applicability to resolve specific problems such as precision underwater measurement, the stability of AFCs of the other kinds has not been investigated in great detail. While filling this knowledge gap is likely to be one of the future directions in AFC research, the lack of long-term stability may be inconsequential in some applications such as, for example, sensing and imaging in in vivo biological environments [ 7 , 183 ] that evolve in time.…”
Section: Discussionmentioning
confidence: 99%
“…However, relatively low viscosity of common liquids such as water implies that Faraday surface waves can be excited using low-amplitude vertical vibrations produced by inexpensive and readily available components such as loudspeakers and piezo-electric transducers ( Figure 17 ) that are much simpler than any equipment used in electrowetting experiments [ 181 ]. As discussed in [ 183 , 184 , 185 ], enhancements of the basic setup used to investigate Faraday waves in oscillating drops also include common elements such as diode lasers, measurement-grade photodetectors and accelerometers, which nevertheless revealed a number of intriguing physical processes that can also help understand the behaviour of smaller drops oscillating at much higher frequencies [ 186 ].…”
Section: Acoustic Frequency Comb Generation Using Vibrations Of Liqui...mentioning
confidence: 99%
“…Here it is important to mention that although other approaches do arrive to the Mathieu equation (11) [12][13][14][15] our approximation allows us to obtain an analytic expression for the Faraday wavevector (15) under the assumption of the balance condition of Eq. (5).…”
Section: Floquet Analysis and Stability Diagrammentioning
confidence: 99%
“…Its study dates back to the 19th century when Michael Faraday first observed them on vertically shaken fluids [2]. Faraday waves are, in fact, a ubiquitous phenomenon in non-linear fluids and have been studied in a large variety of systems such as viscoelastic fluids [3], granular media [4], and even in living soft systems such as earth-worms [5]. Naturally, superfluids are not an exception.…”
Section: Introductionmentioning
confidence: 99%

Faraday Waves in strongly interacting superfluids

Hernández-Rajkov,
Padilla-Castillo,
del Río-Lima
et al. 2021
Preprint
“…For example, Faraday instability can be used to make measurement equipment or measure material parameters, such as measuring the surface tension of soft materials [7], developing new photonic devices [8,9], metamaterials [10,11], etc. In addition, it has potential applications in biology [12] and medicine, such as application in cell culture patterns [13,14] and detecting physiological processes of organisms [15]. It can also be used to monitor and control animal behavior such as earthworms [16], sense and modify soil structure as well as to increase crop yields [17][18][19], medical examinations of medical ultrasound and photoacoustic imaging modalities [20], Brillouin Light Scattering spectroscopy [21], laser vibrometry [22] and develop new methods of eradicating viruses and bacteria [23][24][25].…”
Section: Introductionmentioning
confidence: 99%